O pensamento enxuto aplicado ao processo de vendas complexas: proposição de um método para vendas diretas empresa-consumidor e aplicação a um caso real - Pereira, Bruno Rufato (2008)
Since first contact with Lean Manufacturing, western scientists have been struggling to understand the philosophy and replicate Toyota s benefits. Lean at the industrial environment is well explored and understood. The actual challenge is the expansion to the non-manufacturing arena. This work uses Lean Thinking to solve a sales problem by using its basic principles to reduce demand variability at direct business-to-consumer sales of complex-type buying behavior. Following methodological considerations, the first step towards making up for the research problem was to set Lean Thinking as a Research Program in the molds of Lakatos (1979) providing a common ground for the expansion of its concepts. Second step, covered at chapter three and with rhythm as its fundamental element, was the construction of the proposed method aimed at stabilizing demand through expanding Lean Thinking s principles to sales front-office. This method has been illustrated at chapter four by describing the implementation of the seven proposed steps in a real company over a two year period. Despite this work has not used quantitative or experimental approaches, the proposed method seems to have potential of reducing demand variability in direct business-to-consumer sales. Future research work might test effectiveness of the method by applying it at similar to studied companies or use the Research Program elaborated at chapter two as a foundation to expand Lean Thinking to other non-manufacturing areas, be them sales-related or not.